Factors Associated with Overweight/Obesity among Rural Secondary School Children in Bangladesh (Ibrahim Cardiac Medical Journal, 2024)
Background & Objective: Unhealthy dietary patterns in combination with a sedentary lifestyle could be contributing to some major health issues worldwide. Obesity in children and adolescents can have short- and long-term adverse health consequences including early mortality. Although previously limited to urban areas, with the rapid adoption of urban lifestyle by the rural people the problem is now ubiquitous. It is difficult to develop a policy for promoting health and reducing obesity among adolescents living in rural regions since there is a lack of information on the factors that contribute to this problem. The present study was, therefore undertaken to evaluate the factors influencing overweight and obesity among rural adolescents.Methods: This cross-sectional study was done based on data collected by students of Rajshahi Medical College as part of their RFST (Rural Field-site Training) in 2019 from a rural area of Rajshahi, Bangladesh. A total of 535 students from two rural secondary schools participated in the study. Every alternate student of those schools from class VI-X was then included in the study as a respondent. The weight and height of the selected students were first taken followed by data collection on variables of interest. Using weight and height data, the body mass index (BMI) of the respondents was first determined and was plotted on a growth chart (recommended by CDC, Atlanta) to find the percentile. Then the nutritional status of the individual respondents was determined based on their percentile status and was classified as underweight, normal, overweight, or obese.Results: Almost one-fifth (18.2%) of the respondents was found overweight or obese. Upon comparing respondents’ demographic characteristics, food and exercise behaviour between overweight & obese and normal & underweight groups, the former group was found younger than the latter group. Respondents’ socioeconomic status (SES) was associated with their nutritional status with overweight & obese adolescents being significantly higher in the Middle- and rich SES group (78.4%) than in the poor and lower middle-class (61.4%). Neither dietary nor exercise behaviour was associated with the nutritional status of the respondents. Although the majority (84.2%) of normal & underweight adolescents preferred low to medium-calorie snacks, overweight and obese adolescents were more likely to choose high-calorie snacks. Fast walking and running were the more common forms of exercise behaviour and of longer duration among the overweight & obese cohort than those among normal & underweight cohorts.Conclusion: The study concluded that the period of early adolescence is vulnerable to developing obesity. Adolescents belonging to middle and well-off SES are more prone to be overweight or obese than those belonging to lower middle & poor SES. However, exercise, physical activity, and dietary habits of adolescents do not influence their nutritional status.Ibrahim Card Med J 2023; 13 (1&2): 19-25